Ultraviolet-curable flame-retardant composite resin material as well as preparation method and application thereof
By using ultraviolet-curable flame retardant composite resin material in the battery system of new energy vehicles, the problem that the flame retardant performance, chemical resistance and mechanical properties of the insulating materials are difficult to meet at the same time, and the safety and stability of the battery system under high-voltage fast charging and mechanical stress are achieved.
Patent Information
- Application Number
- CN202510145208.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-05-27
AI Technical Summary
In the battery system of new energy vehicle, the flame retardant properties, chemical resistance and mechanical properties of insulating materials are difficult to meet at the same time, resulting in insufficient safety of the battery system under high-voltage fast charging and mechanical stress.
UV-curable flame retardant composite resin material is used, which is blended with modified acrylates, phosphate modified polyurethane acrylates, phenolic modified acrylates and polyolefin modified polyurethane acrylates, and is prepared by ultraviolet curing technology to improve its flame retardancy, adhesion and insulation properties.
After ultraviolet curing, the material has excellent flame retardant properties (flame retardant level V0), strong adhesion and high insulation resistance. It can maintain stable performance under high voltage fast charging and mechanical stress, ensuring the safety and reliability of the battery system.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of insulating materials, and particularly relates to a UV-curable flame-retardant composite resin material, a preparation method and uses thereof. Background Art
[0002] The essence of new energy vehicles focuses on their power battery and energy storage battery systems, which continuously supply power to the vehicle through a precise series architecture. To optimize space utilization, the battery pack is designed to be extremely compact, with each battery cell closely connected. However, during vehicle operation, especially when encountering bumpy roads or emergency braking, this compact layout may cause the batteries to conduct short circuits due to mutual friction, and in extreme cases, it may lead to fire or even explosion accidents. Therefore, the insulating material covering the battery must have excellent insulation performance to block any potential current leakage. In addition, these insulating materials also need to have excellent toughness and impact resistance to withstand various mechanical stresses during driving. At the same time, the state has introduced three mandatory national standards for new energy vehicles, requiring that in the case of thermal runaway of a single power battery, the system must remain non-fire and non-explosive within 5 minutes, so as to provide sufficient safety evacuation time for vehicle occupants. This strict regulation means that the coating material used in the power battery system must have excellent flame retardancy to effectively contain the spread of fire in extreme cases and provide a solid guarantee for the life safety of occupants.
[0003] To meet the standards and improve the safety of new energy vehicles, the insulating materials for automotive batteries have been optimized. For example, Patent CN116042007A discloses a flame-retardant insulating coating for power batteries and a preparation method thereof. The flame-retardant insulating coating for power batteries of the present invention includes Component A and Component B; Component A includes the following raw materials in parts by weight: 50-70 parts of modified vegetable oil polyol, 15-35 parts of flame-retardant polyol, 10-20 parts of flame retardant, 1-5 parts of flame-retardant synergist, and 0.02-0.5 parts of catalyst; Component B includes the following raw materials in parts by weight: 40-60 parts of isocyanate curing agent; the flame-retardant polyol is a polyol with char-forming properties.
[0004] By adding conventional halogen-based flame retardants, phosphorus-based flame retardants, etc. to the coating, the flame retardant effect has been effectively achieved, but the addition of such flame retardants will greatly reduce the chemical resistance of the insulating material and shorten the service life of the insulating material. Therefore, while ensuring the flame retardancy of the insulating material, the insulating material also needs to be able to withstand higher voltages without breakdown, have stronger impact toughness, excellent bending resistance, and excellent liquid erosion resistance to ensure the absolute safety and stability of the battery system in a high-voltage fast-charging environment.
[0005] In summary, in order to improve the flame retardancy of insulating materials, the insulating materials are often optimized by adding flame retardants. However, the presence of flame retardants affects the chemical resistance of insulating materials. In addition, due to the rapid charging requirements of new energy vehicles and the gradual improvement of safety requirements, the short lifespan, easy shedding, poor insulation and chemical resistance, and unmet flame retardancy requirements of traditional insulating materials remain urgent problems to be solved. Summary of the Invention
[0006] To address the above problems, the present invention provides a UV-curable flame-retardant composite resin material, a preparation method, and uses thereof. The UV-curable flame-retardant composite resin material is prepared by blending a modified acrylate with additives and curing the UV-curable flame-retardant composite resin material by UV curing. The cured UV-curable flame-retardant composite resin material has good chemical resistance, high flame retardancy, and strong adhesion.
[0007] The present invention provides a UV-curable flame-retardant composite resin material, which is prepared by dissolving a modified acrylate in an active diluent, adding an adhesion promoter, a leveling agent, a dispersant, an antifoaming agent, a pigment, a filler, and a photoinitiator, and then curing by UV light. The flame retardancy grade of the UV-curable flame-retardant composite resin material is V0, the adhesion grade is 0, and the pencil hardness is H-2H. The insulation resistance of the UV-curable flame-retardant composite resin material is >1 GΩ, and the leakage current is <0.1 mA. After the UV-curable flame-retardant composite resin material is subjected to impact resistance, bending resistance, electrolyte resistance, salt spray resistance, temperature and humidity resistance, and thermal cycling tests, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, cracking, bubbling, or shedding on the surface. The insulation resistance and leakage current also do not change. The bonding strength of the UV-curable flame-retardant composite resin material after the temperature and humidity resistance test is 12-20 MPa, and the bonding strength of the UV-curable flame-retardant composite resin material after the thermal cycling test is 12-20 MPa.
[0008] Further, the modified acrylate includes phosphate-modified polyurethane acrylate, phenolic-modified acrylate, and polyolefin-modified polyurethane acrylate.
[0009] Further, the components and their contents in the UV-curable flame-retardant composite resin material are as follows: Phosphate-modified polyurethane acrylate: 10-30 parts by weight; Phenolic-modified acrylate: 10-30 parts by weight; Polyolefin-modified polyurethane acrylate: 5-40 parts by weight; Active diluent: 20-60 parts by weight; Adhesion promoter: 1-8 parts by weight; Leveling agent: 0.1 - 0.5 parts by weight; Dispersant: 0.1 - 5 parts by weight; Defoaming agent: 0.1 - 5 parts by weight; Pigment: 1 - 20 parts by weight; Filler: 5 - 30 parts by weight; Photoinitiator: 1 - 8 parts by weight.
[0010] Furthermore, the preparation method of the phosphate-modified polyurethane acrylate is as follows: 2.0 - 2.15 mol of diisocyanate and 0.1 - 1 mol of polyol are stirred and reacted at 100 - 800 r / min and 40 - 85 °C for 0.5 - 4 h, then 1 - 2 mol of phosphate compound is added and the reaction continues for 0.5 - 4 h. Finally, 2.0 - 2.2 mol of capping agent is added and reacted for 2 - 6 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the phosphate-modified polyurethane acrylate.
[0011] Furthermore, the phosphate compound is one or more of trimethylolphosphine oxide, tris(3-hydroxypropyl)phosphine oxide, tris(3-hydroxybutyl)phosphine oxide, bis(3-hydroxypropyl)n-propylphosphine oxide, bis(3-hydroxypropyl)n-butylphosphine oxide, bis(3-hydroxypropyl)sec-butylphosphine oxide, bis(3-hydroxypropyl)phenylphosphine oxide, bis(3-hydroxybutyl)ethylphosphine oxide, and bis(3-hydroxybutyl)n-pentylphosphine oxide.
[0012] Furthermore, when the thickness of the phenolic-modified acrylate is 40 μm, the voltage withstand strength is 6 kV, and when the thickness is 110 μm, the voltage withstand strength is 8 - 11 kV.
[0013] Furthermore, the phenolic-modified acrylate is one or more of phenolic-modified epoxy acrylate and phenolic-modified polyurethane acrylate.
[0014] Furthermore, the modification process of the phenolic-modified epoxy acrylate is as follows: At 40 - 60 °C, 1 mol of o-cresol novolac epoxy resin is added with 0.1 - 0.3% of benzyltriethylammonium chloride based on the total mass of the substances, 300 - 800 ppm of 4-methoxyphenol based on the total mass of the substances, and 100 - 200 ppm of phenothiazine based on the total mass of the substances. Then 1 mol of acrylic acid or methacrylic acid is added and bubbled continuously at 200 mL / min, and the temperature is further raised to 80 - 100 °C and kept warm for 2 - 5 h. When the difference between the acid value in the system and the initial acid value is < 5 mg / KOH / g and the epoxy value is < 0.03, the reaction ends to obtain the phenolic-modified epoxy acrylate.
[0015] Furthermore, the modification process of the phenolic-modified polyurethane acrylate is as follows: 2.0 - 2.15 mol of diisocyanate is added dropwise to 0.1 - 1 mol of polyol, and the mixture is stirred and heated to 40 - 85 °C at 300 - 500 r / min. After reacting for 0.5 - 4 h, 0.2 - 2 mol of o-cresol formaldehyde resin is added, and the reaction continues for 0.5 - 4 h. Finally, 2.0 - 2.2 mol of a capping agent is added and reacted for 2 - 6 h. The reaction is terminated when the NCO content in the system is lower than 0.1% at 40 - 85 °C to obtain phenolic-modified polyurethane acrylate.
[0016] Furthermore, the water absorption rate of the polyolefin-modified polyurethane acrylate after being immersed in normal-temperature water for 1000 h is 0.15%. After being immersed in normal-temperature electrolyte for 1000 h, after 2000 cycles of thermal cycling at -40 to 85 °C, and after steaming at 85 °C and 1000% RH for 1000 h, there are no bubbles, no peeling, and it has insulation withstand voltage.
[0017] Furthermore, the modification process of the polyolefin-modified polyurethane acrylate is as follows: 2.0 - 2.15 mol of diisocyanate and 0.1 - 1 mol of polyol are stirred and reacted at 100 - 800 r / min and 40 - 85 °C for 0.5 - 4 h. Then 1 - 2 mol of polyolefin is added, and the reaction continues for 0.5 - 4 h. Finally, 2.0 - 2.2 mol of a capping agent is added and reacted for 2 - 6 h. The reaction is terminated when the NCO content in the system is lower than 0.1% to obtain the polyolefin-modified polyurethane acrylate.
[0018] Furthermore, the polyolefin in the polyolefin-modified polyurethane acrylate is one or more of polybutadiene, polybutadiene-acrylonitrile, and polybutadiene-styrene.
[0019] Furthermore, in the modification processes of the phosphate-modified polyurethane acrylate, the phenolic-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate, the diisocyanate is one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), xylylene diisocyanate (XDI), 2,2,4-trimethylhexane diisocyanate (TMDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI).
[0020] Further, during the modification of the phosphate-modified polyurethane acrylate, the phenolic-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate, the polyol is one or more of polypropylene glycol, polypropylene glycol, polypropylene triol, polycaprolactone diol, polytetrahydrofuran diol, polyhexylene adipate diol, polyneopentyl adipate diol, polyethylene adipate diol, polyethylene glycol propylene glycol adipate diol, polycarbonate diol, polyneopentyl isophthalate adipate diol, castor oil, and castor oil derivatives.
[0021] Further, during the modification of the phenolic-modified polyurethane acrylate and the polyolefin-modified polyurethane acrylate, the capping agent is one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
[0022] Further, the active diluent is one or more of (ethoxy)phenol acrylate, 2-(propoxy)nonylphenol acrylate, phenyl methacrylate, benzyl acrylate, benzyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, dicyclopentene ester, isobornyl acrylate, isobornyl methacrylate, acryloylmorpholine, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, 4-tert-butylcyclohexyl acrylate, 4-tert-butylcyclohexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isodecyl acrylate, isodecyl methacrylate, lauryl acrylate, lauryl methacrylate, stearyl acrylate, stearyl methacrylate, bisphenol fluorene diacrylate, ethoxylated bisphenol fluorene diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, dipropylene glycol diacrylate, diethylene glycol diacrylate, 1,3-propanediol dimethacrylate, dipropylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, diallyl isocyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, bis-trimethylolpropane tetraacrylate, isocyanuric acid triacrylate, pentaerythritol triacrylate, and dipentaerythritol hexaacrylate.
[0023] Further, the adhesion promoter is one or more of titanate, monofunctional acid ester modifier, trifunctional phosphate ester modifier, 3-acryloxypropyltrimethoxysilane, and tetra-neoalkoxy bis(didecyl phosphite acyloxy)titanate.
[0024] Further, the leveling agent is a polyether siloxane copolymer.
[0025] Further, the dispersant is a polymer segment with an amphiphilic molecular structure, and the amphiphilic molecular structure includes a pigmentophilic group and a solventophilic group; The pigmentophilic group is a polar group, including one or more of carboxyl group, sulfonic acid group, and amine group; The solventophilic group is a non-polar group, including one or more of long-chain hydrocarbon groups and polyether segments; The polymer segment includes one or more of acrylic polymers and polyether polymers.
[0026] Further, the density of the dispersant is 0.94 - 1.06 kg / m³.
[0027] Further, the defoaming agent is one or more of silicone-free defoaming agents, organically modified polysiloxanes, and self-emulsifying defoaming agents.
[0028] Further, the pigment is one or more of iron oxide black, carbon black, titanium dioxide, iron oxide yellow, iron oxide red, phthalocyanine blue, and phthalocyanine green.
[0029] Further, the filler includes one or more of mica powder, barium sulfate, kaolin, talc powder, silica powder, alumina, fumed silica, polytetrafluoroethylene wax powder, zinc phosphate, glass flakes, calcium ion exchange type rust-inhibiting pigment, magnesium dihydrogen phosphate, and zinc phosphomolybdate.
[0030] Further, the photoinitiator includes one or more of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPPO), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), 4-chlorobenzophenone, methyl o-benzoylbenzoate, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, benzophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2,2-dimethoxy-2-phenylacetophenone, and 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone.
[0031] The present invention also provides a preparation method of the ultraviolet-curable flame-retardant composite resin material, including the following steps: Step 1: Place phosphate-modified polyurethane acrylate, phenolic-modified acrylate, polyolefin-modified polyurethane acrylate, active diluent, dispersant, and defoaming agent in a mixing tank and stir and mix to obtain a mixed material; Step 2: Add the pigment and filler to the mixing tank, continue to stir and mix with the mixed material, and sand the mixture after mixing evenly to obtain a fine material; Step 3: Add the adhesion promoter, leveling agent and photoinitiator into the mixing tank, continue to stir and mix with the fine materials, and filter to obtain a liquid coating precursor; Step 4: Spray the coating precursor into a film and cure it to obtain the ultraviolet-curable flame-retardant composite resin material.
[0032] Further, the mass ratio of the phosphoric acid ester-modified polyurethane acrylate, the phenolic aldehyde-modified acrylate, the polyolefin-modified polyurethane acrylate, the reactive diluent, the dispersant and the defoamer in the step 1 is (10 - 30):(10 - 30):(5 - 40):(20 - 60):(0.1 - 5):(0.1 - 5).
[0033] Further, the preparation method of the phosphoric acid ester-modified polyurethane acrylate in the step 1 is as follows: React 2.0 - 2.15 mol of diisocyanate with 0.1 - 1 mol of polyol at 100 - 800 r / min and 40 - 85 °C for 0.5 - 4 h, then add 1 - 2 mol of phosphoric acid ester compound and continue to react for 0.5 - 4 h. Finally, add 2.0 - 2.2 mol of capping agent and react for 2 - 6 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the phosphoric acid ester-modified polyurethane acrylate.
[0034] Further, the phosphoric acid ester compound is one or more of trimethylolphosphine oxide, tris(3-hydroxypropyl)phosphine oxide, tris(3-hydroxybutyl)phosphine oxide, bis(3-hydroxypropyl)n-propylphosphine oxide, bis(3-hydroxypropyl)n-butylphosphine oxide, bis(3-hydroxypropyl)sec-butylphosphine oxide, bis(3-hydroxypropyl)phenylphosphine oxide, bis(3-hydroxybutyl)ethylphosphine oxide and bis(3-hydroxybutyl)n-pentylphosphine oxide.
[0035] Further, when the thickness of the phenolic aldehyde-modified acrylate in the step 1 is 40 μm, the withstand voltage strength is 6 kV, and when the thickness is 110 μm, the withstand voltage strength is 8 - 11 kV.
[0036] Further, the phenolic aldehyde-modified acrylate in the step 1 is one or more of phenolic aldehyde-modified epoxy acrylate and phenolic aldehyde-modified polyurethane acrylate.
[0037] Further, the modification process of the phenolic aldehyde-modified epoxy acrylate is as follows: At 40 - 60 °C, add 1 mol of o-cresol novolac epoxy resin, 0.1 - 0.3% of benzyltriethylammonium chloride based on the total mass of the substances, 300 - 800 ppm of 4-methoxyphenol based on the total mass of the substances, and 100 - 200 ppm of phenothiazine based on the total mass of the substances. Then add 1 mol of acrylic acid or methacrylic acid and continuously bubble at 200 mL / min. Continue heating to 80 - 100 °C and keep warm for 2 - 5 h until the difference between the acid value in the system and the initial acid value is < 5 mg / KOH / g and the epoxy value is < 0.03, then the reaction ends to obtain phenol-formaldehyde modified epoxy acrylate.
[0038] Furthermore, the modification process of the phenol-formaldehyde modified polyurethane acrylate is as follows: Drop 0.1 - 1 mol of polyol into 2.0 - 2.15 mol of isocyanate, stir and heat to 40 - 85 °C at 300 - 500 r / min, react for 0.5 - 4 h, then add 0.2 - 2 mol of o-cresol resin, continue to react for 0.5 - 4 h, and finally add 2.0 - 2.2 mol of end-capping agent and react for 2 - 6 h. When the NCO content in the system is lower than 0.1% at 40 - 85 °C, the reaction ends to obtain phenol-formaldehyde modified polyurethane acrylate.
[0039] Furthermore, the water absorption rate of the polyolefin-modified polyurethane acrylate in step 1 after soaking in normal-temperature water for 1000 h is 0.15%. After soaking in normal-temperature electrolyte for 1000 h, after 2000 h of thermal cycling at -40 to 85 °C, and after steaming at 85 °C and 1000% RH for 1000 h, there are no bubbles, no peeling, and it has insulation withstand voltage.
[0040] Furthermore, the modification process of the polyolefin-modified polyurethane acrylate in step 1 is as follows: React 2.0 - 2.15 mol of diisocyanate with 0.1 - 1 mol of polyol at 100 - 800 r / min and 40 - 85 °C for 0.5 - 4 h, then add 1 - 2 mol of polyolefin, continue to react for 0.5 - 4 h, and finally add 2.0 - 2.2 mol of end-capping agent and react for 2 - 6 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the polyolefin-modified polyurethane acrylate.
[0041] Furthermore, the polyolefin in the polyolefin-modified polyurethane acrylate is one or more of polybutadiene, polybutadiene-acrylonitrile, and polybutadiene-styrene.
[0042] Further, in the modification processes of the phosphate-modified polyurethane acrylate, the phenolic-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate, the diisocyanate is one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), xylylene diisocyanate (XDI), 2,2,4-trimethylhexane diisocyanate (TMDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI).
[0043] Further, in the modification processes of the phosphate-modified polyurethane acrylate, the phenolic-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate, the polyol is one or more of polypropylene glycol, polypropylene glycol, polypropylene triol, polycaprolactone diol, polytetrahydrofuran diol, hexanediol adipate diol, neopentyl glycol adipate diol, diethylene glycol adipate diol, ethylene glycol propylene glycol adipate diol, polycarbonate diol, neopentyl glycol isophthalate adipate diol, castor oil, and castor oil derivatives.
[0044] Further, in the modification processes of the phenolic-modified polyurethane acrylate and the polyolefin-modified polyurethane acrylate, the blocking agent is one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
[0045] Further, the reactive diluent in the step 1 is one or more of (ethoxy)phenol acrylate, 2-(propoxy)nonylphenol acrylate, phenyl methacrylate, benzyl acrylate, benzyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, dicyclopentenyloxyethyl acrylate, isobornyl acrylate, isobornyl methacrylate, acryloylmorpholine, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, 4-tert-butylcyclohexyl acrylate, 4-tert-butylcyclohexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isodecyl acrylate, isodecyl methacrylate, lauryl acrylate, lauryl methacrylate, stearyl acrylate, stearyl methacrylate, bisphenol fluorene diacrylate, ethoxylated bisphenol fluorene diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, dipropylene glycol diacrylate, diethylene glycol diacrylate, 1,3-propanediol dimethacrylate, dipropylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, diallyl isocyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, isocyanuric acid triacrylate, pentaerythritol triacrylate, and dipentaerythritol hexaacrylate.
[0046] Further, the dispersant in the step 1 is a polymer segment with an amphiphilic molecular structure, and the amphiphilic molecular structure includes a pigmentophilic group and a solventophilic group; The pigmentophilic group is a polar group, including one or more of a carboxyl group, a sulfonic acid group, and an amine group; The solventophilic group is a non-polar group, including one or more of a long-chain hydrocarbon group and a polyether segment; The polymer segment includes one or more of an acrylic polymer and a polyether polymer.
[0047] Further, the density of the dispersant in the step 1 is 0.94 - 1.06 kg / m³.
[0048] Further, the defoamer in the step 1 is one or more of a silicone-free defoamer, an organically modified polysiloxane, and a self-emulsifying defoamer.
[0049] Further, the stirring speed in the step 1 is 500 - 1500 r / min, and the stirring time is 15 - 45 min.
[0050] Further, the mass ratio of the pigment, the filler, and the phenolic modified acrylate in step 2 is (1 - 20):(5 - 30):(10 - 30).
[0051] Further, the pigment in step 2 includes one or more of iron oxide black, carbon black, titanium dioxide, iron oxide yellow, iron oxide red, phthalocyanine blue, and phthalocyanine green.
[0052] Further, the filler in step 2 includes one or more of mica powder, barium sulfate, kaolin, talc powder, silica powder, alumina, fumed silica, polytetrafluoroethylene wax powder, zinc phosphate, glass flakes, calcium ion exchange type rust preventive pigment, magnesium dihydrogen phosphate, and zinc phosphomolybdate.
[0053] Further, the speed of continuous stirring in step 2 is 500 - 1500 r / min, and the time of continuous stirring is 15 - 45 min.
[0054] Further, the fineness of the fine material in step 2 is < 15 μm.
[0055] Further, the mass ratio of the adhesion promoter, the leveling agent, the photoinitiator, and the phenolic modified acrylate in step 3 is (1 - 8):(0.1 - 0.5):(1 - 8):(10 - 30).
[0056] Further, the adhesion promoter in step 3 includes one or more of titanate, monofunctional acid ester modifier, trifunctional phosphate ester modifier, 3 - acryloxypropyltrimethoxysilane, and tetraalkoxy bis(didecyl phosphite) titanate.
[0057] Further, the leveling agent in step 3 is a polyether silicone copolymer.
[0058] Further, the photoinitiator in step 3 includes one or more of 2 - hydroxy - 2 - methylacetophenone, 1 - hydroxycyclohexyl phenyl ketone, diphenyl(2,4,6 - trimethylbenzoyl)phosphine oxide (TPPO), phenylbis(2,4,6 - trimethylbenzoyl)phosphine oxide (TPO), 4 - chlorobenzophenone, methyl o - benzoylbenzoate, 2 - isopropylthioxanthone, ethyl 4 - dimethylaminobenzoate, benzophenone, 2 - benzyl - 2 - dimethylamino - 1 - (4 - morpholinophenyl)butanone, 2,2 - dimethoxy - 2 - phenylacetophenone, and 2 - methyl - 2 - (4 - morpholinyl)-1 - [4 - (methylthio)phenyl]-1 - propanone.
[0059] Further, the speed of continuous stirring in step 3 is 500 - 1500 r / min, and the time of continuous stirring is 15 - 45 min.
[0060] Further, the pressure of the spraying in step 4 is 1.5 - 4 bar, and the distance of the spraying is 15 - 25 cm.
[0061] Further, the thickness of the film in step 4 is 80 - 130 μm.
[0062] Further, the curing speed in step 4 is 1 - 20 m / min, the curing method is ultraviolet curing, and the irradiation intensity of the ultraviolet light is 300 - 500 mW / cm 2 .
[0063] The present invention also provides an electrical insulation outer layer, and the electrical insulation outer layer is prepared from the ultraviolet - curable flame - retardant composite resin material.
[0064] Advantages of the present invention: 1. In the present invention, by using phosphate - modified polyurethane acrylate to replace the traditional halogen - based flame retardant, no toxic and harmful substances such as hydrogen halide are released during the combustion of the material. During the combustion of phosphate - modified polyurethane acrylate, the phosphate groups can promote the formation of a dense carbon layer on the surface of the polymer, effectively isolating oxygen and heat, preventing the spread of the flame and the transfer of heat. In addition, phenolic - modified acrylate and polyolefin - modified polyurethane acrylate of the same system are added to the material. As an organic polymer material, phosphate - modified polyurethane acrylate has good compatibility with acrylate materials of the same system, can form stable chemical bonding or physical entanglement with phenolic - modified acrylate and polyolefin - modified polyurethane acrylate, is evenly dispersed in the material, and no agglomeration or phase separation phenomenon occurs, thus ensuring that the mechanical properties and processing properties of the material are not affected; 2. The polymer structure formed after the curing of phenolic - modified acrylate in the present invention is compact, which can effectively prevent the conduction of charges, making the material have a high volume resistivity, and can withstand a high voltage under the action of an electric field without breakdown, greatly reducing the risk of electric leakage, ensuring the safe operation of electrical equipment, and at the same time, having good temperature and corrosion resistance; in polyolefin - modified polyurethane acrylate, the polyolefin and acrylate structures result in small water absorption and swelling. In a humid environment, it can maintain stable insulation performance, avoiding the decline of insulation performance due to water absorption, and is suitable for electrical equipment in humid environments such as outdoors and underwater. It also has good tolerance to common acids, alkalis, organic solvents and other chemical substances. Moreover, the long - chain structure of polyolefin in polyolefin - modified polyurethane acrylate can also play an internal plasticization role, interpenetrating with phenolic - modified acrylate and phosphate - modified polyurethane acrylate at the molecular level to form a uniform mixed system, enhancing the electrical properties of the ultraviolet - curable flame - retardant composite resin material during use, and also improving the temperature, humidity and corrosion resistance of the ultraviolet - curable flame - retardant composite resin material; 3. In the present invention, additives such as reactive diluents, leveling agents, dispersants, defoamers, pigments, and fillers are also added. The phosphate - modified polyurethane acrylate, phenolic - modified acrylate, and polyolefin - modified polyurethane acrylate are dissolved in the reactive diluent, and then pigments and fillers are added for mixing to prevent aggregation and caking due to the large particle size or high content of pigments and fillers. At the same time, in the present invention, the particle size is ground to 15 μm by sanding, making the formed material more dense, reducing the pores and defects in the material, thereby effectively improving the insulation performance of the material and reducing the risk of leakage and breakdown. Finally, an adhesion promoter, a leveling agent, and a photo - initiator are added to prevent the adhesion promoter and the leveling agent from undergoing thermal decomposition during the sanding process. At the same time, during the preparation process, the photo - initiator is prevented from being partially inactivated due to long - term exposure to natural light. After mixing, it is cured by ultraviolet irradiation. The ultraviolet curing speed is fast, and it is friendly to heat - intolerant substrates, and will not deform due to the heat - intolerance of the substrate. At the same time, the cross - linking density of the ultraviolet - curable flame - retardant composite resin material after ultraviolet curing is high. Detailed Embodiments
[0065] The following is a detailed description of the invention in combination with embodiments: The present invention provides an ultraviolet - curable flame - retardant composite resin material, a preparation method, and uses thereof. By blending phosphate - modified polyurethane acrylate, phenolic - modified acrylate, polyolefin - modified polyurethane acrylate and other additives, its flame - retardant performance and insulation performance are greatly improved.
[0066] Example 1 This example provides an ultraviolet - curable flame - retardant composite resin material. The ultraviolet - curable flame - retardant composite resin material is prepared by dissolving modified acrylate in a reactive diluent, and then adding an adhesion promoter, a leveling agent, a dispersant, a defoamer, pigments, fillers, and a photo - initiator for mixing, and then curing by ultraviolet irradiation. The flame - retardant grade of the ultraviolet - curable flame - retardant composite resin material is V0, the adhesion grade is 0, and the pencil hardness is H. The insulation resistance of the ultraviolet - curable flame - retardant composite resin material is > 1 GΩ, and the leakage current is < 0.1 mA. After the ultraviolet - curable flame - retardant composite resin material undergoes impact resistance, bending resistance, electrolyte resistance, salt spray resistance test, temperature and humidity resistance, and thermal cycling resistance tests, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, no cracking, no bubbling, and no peeling on the surface. The insulation resistance and leakage current do not change. And the bonding strength of the ultraviolet - curable flame - retardant composite resin material after the temperature and humidity resistance test is 15.8 MPa, and the bonding strength of the ultraviolet - curable flame - retardant composite resin material after the thermal cycling resistance test is 16.3 MPa.
[0067] In this embodiment, the modified acrylate includes phosphate-modified polyurethane acrylate, phenolic-modified acrylate, and polyolefin-modified polyurethane acrylate. The phenolic-modified acrylate is phenolic-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate is polybutadiene-modified polyurethane acrylate.
[0068] In this embodiment, the components and their contents in the ultraviolet-curable flame-retardant composite resin material are as follows: Phosphate-modified polyurethane acrylate: 10 parts by weight; Phenolic-modified polyurethane acrylate: 10 parts by weight; Polybutadiene-modified polyurethane acrylate: 10 parts by weight; Reactive diluent: 35 parts by weight; Adhesion promoter: 3 parts by weight; Leveling agent: 0.3 parts by weight; Dispersant: 1 part by weight; Defoaming agent: 0.5 parts by weight; Pigment: 5.2 parts by weight; Filler: 20 parts by weight; Photoinitiator: 5 parts by weight; The preparation method of the phosphate-modified polyurethane acrylate is as follows: React 2.15 mol of toluene diisocyanate with 1 mol of polytetrahydrofuran glycol by stirring at 500 r / min and 65 °C for 2 h, then add 1 mol of trimethylol phosphine oxide and continue to react for 2 h. Finally, add 2.2 mol of hydroxyethyl acrylate and react for 4 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the phosphate-modified polyurethane acrylate; The modification process of the phenolic-modified polyurethane acrylate is as follows: Dropwise add 1 mol of polytetrahydrofuran glycol to 2.0 mol of toluene diisocyanate, stir and react at 500 r / min and 65 °C for 2 h, add 1 mol of o-cresol formaldehyde resin, continue to react for 2 h, and finally add 2.2 mol of hydroxyethyl acrylate and react for 4 h. When the NCO content in the system is lower than 0.1% at 65 °C, the reaction ends to obtain the phenolic-modified polyurethane acrylate; The modification process of the polybutadiene-modified polyurethane acrylate is as follows: React 2.15 mol of toluene diisocyanate with 1 mol of polytetrahydrofuran glycol by stirring at 500 r / min and 65 °C for 2 h, then add 1 mol of polybutadiene and continue to react for 2 h. Finally, add 2.2 mol of hydroxyethyl acrylate and react for 4 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the polybutadiene-modified polyurethane acrylate; The reactive diluent is 20 parts by weight of isobornyl methacrylate and 15 parts by weight of isodecyl acrylate; The adhesion promoter is a tri-functional phosphate ester modifier, manufactured by Arkema, with the product number SR9051; The leveling agent is a polyether silicone copolymer, manufactured by BYK, with the product number BYK379; The dispersant has a polymer segment with an amphiphilic molecular structure, with the product number Lencolo 1108; The defoamer is a silicone-free defoamer, manufactured by Degussa, with the product number TEGO920; The pigments are 0.2 parts by weight of iron oxide red, 1 part by weight of iron oxide yellow, and 5 parts by weight of titanium dioxide; The fillers include 15 parts by weight of mica powder and 3 parts by weight of zinc phosphomolybdate; The photoinitiators include 3 parts by weight of 1-hydroxycyclohexyl phenyl ketone and 2 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0069] This example also provides a method for preparing the ultraviolet-curable flame-retardant composite resin material, which includes the following steps: Step 1: Place the phosphate ester-modified polyurethane acrylate, phenol-formaldehyde-modified polyurethane acrylate, polybutadiene-modified polyurethane acrylate, reactive diluent, dispersant, and defoamer in a mixing tank and stir and mix at 300 r / min for 5 min to obtain a mixed material; Step 2: Add the pigments and fillers to the mixing tank, continue to stir and mix with the mixed material at 300 r / min for 5 min, and then perform sanding after mixing evenly to obtain a fine material with a fineness < 15 μm; Step 3: Add the adhesion promoter, leveling agent, and photoinitiator to the mixing tank, continue to stir and mix with the fine material at 300 r / min for 5 min, and filter to obtain a liquid paint precursor; Step 4: After spraying the paint precursor into a film with a thickness of 100 μm, cure it at a speed of 5 m / min under an irradiation intensity of 300 mW / cm 2 The spraying pressure is 1.5 bar, and the spraying distance is 15 cm to obtain the ultraviolet-curable flame-retardant composite resin material.
[0070] Example 2 This embodiment provides a UV-curable flame-retardant composite resin material. The UV-curable flame-retardant composite resin material is prepared by dissolving a modified acrylate in an active diluent, and then adding an adhesion promoter, a leveling agent, a dispersant, an antifoaming agent, a pigment, a filler, and a photoinitiator and mixing them, followed by UV curing; the flame-retardant grade of the UV-curable flame-retardant composite resin material is V0, the adhesion grade is grade 0, and the pencil hardness is H-2H; the insulation resistance of the UV-curable flame-retardant composite resin material is >1 GΩ, and the leakage current is <0.1 mA; After the UV-curable flame-retardant composite resin material undergoes impact resistance, bending resistance, electrolyte resistance, salt spray resistance test, temperature and humidity resistance, and thermal cycling resistance, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, no cracking, no bubbling, and no peeling on the surface. The insulation resistance and leakage current do not change. Moreover, the bonding strength of the UV-curable flame-retardant composite resin material after the temperature and humidity resistance test is 16.9 MPa, and the bonding strength of the UV-curable flame-retardant composite resin material after the thermal cycling resistance test is 17.2 MPa.
[0071] In this embodiment, the modified acrylate includes phosphate-modified polyurethane acrylate, phenolic-modified acrylate, and polyolefin-modified polyurethane acrylate. The phenolic-modified acrylate is phenolic-modified epoxy acrylate, and the polyolefin-modified polyurethane acrylate is polybutadiene-modified polyurethane acrylate.
[0072] In this embodiment, the components and their contents in the UV-curable flame-retardant composite resin material are as follows: Phosphate-modified polyurethane acrylate: 13 parts by weight; Phenolic-modified epoxy acrylate: 10 parts by weight; Polybutadiene-modified polyurethane acrylate: 5 parts by weight; Active diluent: 30 parts by weight; Adhesion promoter: 5 parts by weight; Leveling agent: 0.5 part by weight; Dispersant: 1 part by weight; Antifoaming agent: 0.5 part by weight; Pigment: 5.5 parts by weight; Filler: 27 parts by weight; Photoinitiator: 2.5 parts by weight; The preparation method of the phosphate-modified polyurethane acrylate is as follows: 2.15 mol of toluene diisocyanate and 1 mol of polytetrahydrofuran diol were stirred and reacted at 500 r / min and 65 °C for 2 h. Then, 1 mol of phosphine oxide trimethanol was added and the reaction continued for 2 h. Finally, 2.2 mol of hydroxyethyl acrylate was added and the reaction proceeded for 4 h. The reaction was terminated when the NCO content in the system was less than 0.1%, and the phosphate-modified polyurethane acrylate was obtained. The modification process of the phenolic aldehyde-modified epoxy acrylate is as follows: At 40 °C, 1 mol of o-cresol novolac epoxy resin was added with 0.3% of benzyltriethylammonium chloride based on the total mass of the substances, 500 ppm of 4-methoxyphenol based on the total mass of the substances, and 100 ppm of phenothiazine based on the total mass of the substances. Then, 1 mol of acrylic acid was added and continuous bubbling was carried out at 200 mL / min. The temperature was further raised to 80 °C and kept warm for 3 h. When the difference between the acid value in the system and the initial acid value was < 5 mg KOH / g and the epoxy value was < 0.03, the reaction ended, and the phenolic aldehyde-modified epoxy acrylate was obtained. The modification process of the polybutadiene-modified polyurethane acrylate is as follows: 2.15 mol of toluene diisocyanate and 1 mol of polytetrahydrofuran diol were stirred and reacted at 500 r / min and 65 °C for 2 h. Then, 1 mol of polybutadiene was added and the reaction continued for 2 h. Finally, 2.2 mol of hydroxyethyl acrylate was added and the reaction proceeded for 4 h. The reaction was terminated when the NCO content in the system was less than 0.1%, and the polybutadiene-modified polyurethane acrylate was obtained. The active diluent is 30 parts by weight of isobornyl acrylate. The adhesion promoter is titanate. The leveling agent is a polyether silicone copolymer, manufactured by BYK, with the product number BYK3760. The dispersant has a polymer segment with an amphiphilic molecular structure, which is an acrylic copolymer, manufactured by BYK, with the product number BYK-2013. The defoaming agent is a silicone-free defoaming agent, manufactured by Degussa, with the product number TEGO900. The pigments are 0.5 part by weight of phthalocyanine blue and 5 parts by weight of titanium dioxide. The fillers include 25 parts by weight of mica powder and 2 parts by weight of zinc phosphate. The photoinitiators include 1.5 parts by weight of 2-hydroxy-2-methylpropiophenone and 1 part by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0073] This example also provides a method for preparing the ultraviolet-curable flame-retardant composite resin material, which includes the following steps: Step 1: Put phosphate-modified polyurethane acrylate, phenolic-modified epoxy acrylate, polybutadiene-modified polyurethane acrylate, reactive diluent, dispersant and defoamer into a mixing tank and stir and mix them at 500 r / min for 3 min to obtain a mixed material; Step 2: Add pigments and fillers to the mixing tank, continue to stir and mix them with the mixed material at 500 r / min for 3 min, and then perform sanding after mixing evenly to obtain a fine material with a fineness < 15 μm; Step 3: Add adhesion promoter, leveling agent and photoinitiator to the mixing tank, continue to stir and mix them with the fine material at 500 r / min for 3 min, and filter to obtain a liquid coating precursor; Step 4: After spraying the coating precursor into a film with a thickness of 120 μm, cure it at a speed of 5 m / min under an irradiation intensity of 500 mW / cm 2 , the spraying pressure is 3 bar, and the spraying distance is 20 cm to obtain the ultraviolet-curable flame-retardant composite resin material.
[0074] Comparative Example 1 This comparative example provides an ultraviolet-curable flame-retardant composite resin material, which is prepared by dissolving modified acrylate in a reactive diluent, then adding an adhesion promoter, a leveling agent, a dispersant, a defoamer, pigments, fillers and a photoinitiator and mixing, and then curing by ultraviolet rays; the flame-retardant grade of the ultraviolet-curable flame-retardant composite resin material is V1, the adhesion grade is 0 grade, and the pencil hardness is 2H; the insulation resistance of the ultraviolet-curable flame-retardant composite resin material > 1 GΩ, and the leakage current < 0.1 mA; After the ultraviolet-curable flame-retardant composite resin material is subjected to impact resistance, bending resistance, electrolyte resistance, salt spray test, temperature and humidity resistance and thermal cycling, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, no crack, no bubbling, no peeling on the surface, and the insulation resistance and leakage current do not change. Moreover, the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the temperature and humidity resistance test is 14.5 MPa, and the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the thermal cycling test is 15.8 MPa.
[0075] In this comparative example, the modified acrylate includes phenolic-modified acrylate and polyolefin-modified polyurethane acrylate, the phenolic-modified acrylate is phenolic-modified epoxy acrylate, and the polyolefin-modified polyurethane acrylate is polybutadiene-modified polyurethane acrylate.
[0076] In this comparative example, the components and their contents in the ultraviolet-curable flame-retardant composite resin material are as follows: Phenolic-modified epoxy acrylate: 10 parts by weight; Polybutadiene-modified polyurethane acrylate: 5 parts by weight; Reactive diluent: 30 parts by weight; Adhesion promoter: 5 parts by weight; Leveling agent: 0.5 parts by weight; Dispersant: 1 part by weight; Defoamer: 0.5 parts by weight; Pigment: 5.5 parts by weight; Filler: 27 parts by weight; Photoinitiator: 2.5 parts by weight; The modification process of the phenolic aldehyde-modified epoxy acrylate is as follows: At 40 °C, add 1 mol of o-cresol novolac epoxy resin, 0.3% of benzyltriethylammonium chloride based on the total mass of the substances, 500 ppm of 4-methoxyphenol based on the total mass of the substances, and 100 ppm of phenothiazine based on the total mass of the substances. Then add 1 mol of acrylic acid and continuously bubble at 200 mL / min. Continue to heat to 80 °C and hold for 3 h. When the difference between the acid value in the system and the initial acid value is < 5 mg / KOH / g and the epoxy value is < 0.03, the reaction ends to obtain the phenolic aldehyde-modified epoxy acrylate; The modification process of the polybutadiene-modified polyurethane acrylate is as follows: React 2.15 mol of toluene diisocyanate with 1 mol of polytetrahydrofuran diol by stirring at 500 r / min and 65 °C for 2 h. Then add 1 mol of polybutadiene and continue to react for 2 h. Finally, add 2.2 mol of hydroxyethyl acrylate and react for 4 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the polybutadiene-modified polyurethane acrylate; The reactive diluent is 30 parts by weight of isobornyl acrylate; The adhesion promoter is titanate; The leveling agent is a polyether silicone copolymer, manufactured by BYK, with the product number BYK3760; The dispersant has a polymer chain segment with an amphiphilic molecular structure, is an acrylic copolymer, manufactured by BYK, with the product number BYK-2013; The defoamer is a silicone-free defoamer, manufactured by Degussa, with the product number TEGO900; The pigment is 0.5 parts by weight of phthalocyanine blue and 5 parts by weight of titanium dioxide; The filler includes 25 parts by weight of mica powder and 2 parts by weight of zinc phosphate; The photoinitiator includes 1.5 parts by weight of 2-hydroxy-2-methylpropiophenone and 1 part by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0077] This comparative example also provides a method for preparing the ultraviolet-curable flame-retardant composite resin material, which includes the following steps: Step 1: Place phenolic-modified epoxy acrylate, polybutadiene-modified polyurethane acrylate, active diluent, dispersant, and defoamer in a mixing tank and stir and mix them at 500 r / min for 3 min to obtain a mixed material; Step 2: Add pigment and filler to the mixing tank, continue to stir and mix with the mixed material at 500 r / min for 3 min, and perform sanding after mixing evenly to obtain a fine material with a fineness < 15 μm; Step 3: Add adhesion promoter, leveling agent, and photoinitiator to the mixing tank, continue to stir and mix with the fine material at 500 r / min for 3 min, and filter to obtain a liquid paint precursor; Step 4: After spraying the paint precursor into a film with a thickness of 120 μm, cure it at a speed of 5 m / min under an irradiation intensity of 500 mW / cm 2 The spraying pressure is 4 bar, and the spraying distance is 25 cm to obtain the ultraviolet-curable flame-retardant composite resin material.
[0078] Comparative Example 2 This comparative example provides an ultraviolet-curable flame-retardant composite resin material. The ultraviolet-curable flame-retardant composite resin material is prepared by dissolving modified acrylate in an active diluent, and then adding an adhesion promoter, leveling agent, dispersant, defoamer, pigment, filler, and photoinitiator and mixing them, followed by ultraviolet curing; the flame-retardant grade of the ultraviolet-curable flame-retardant composite resin material is V0, the adhesion grade is grade 0, and the pencil hardness is B; the insulation resistance of the ultraviolet-curable flame-retardant composite resin material > 1 GΩ, and the leakage current < 0.1 mA; After the ultraviolet-curable flame-retardant composite resin material is subjected to impact resistance, bending resistance, electrolyte resistance, salt spray test, temperature and humidity resistance, and thermal cycling resistance, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, no crack, no shedding on the surface, and the insulation resistance and leakage current do not change, but there are bubbles, and the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the temperature and humidity resistance test is 11.7 MPa, and the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the thermal cycling resistance test is 11.6 MPa.
[0079] In this comparative example, the modified acrylate includes phosphate-modified polyurethane acrylate and polyolefin-modified polyurethane acrylate, and the polyolefin-modified polyurethane acrylate is polybutadiene-modified polyurethane acrylate.
[0080] In this comparative example, the components and their contents in the ultraviolet-curable flame-retardant composite resin material are as follows: Phosphate-modified polyurethane acrylate: 13 parts by weight; Polybutadiene-modified polyurethane acrylate: 5 parts by weight; Reactive diluent: 30 parts by weight; Adhesion promoter: 5 parts by weight; Leveling agent: 0.5 parts by weight; Dispersant: 1 part by weight; Defoaming agent: 0.5 parts by weight; Pigment: 5.5 parts by weight; Filler: 27 parts by weight; Photoinitiator: 2.5 parts by weight; The preparation method of the phosphate-modified polyurethane acrylate is as follows: 2.15 mol of toluene diisocyanate and 1 mol of polytetrahydrofuran diol are stirred and reacted at 500 r / min and 65 °C for 2 h, then 1 mol of trimethylol phosphine oxide is added and the reaction continues for 2 h. Finally, 2.2 mol of hydroxyethyl acrylate is added and the reaction proceeds for 4 h. When the NCO content in the system is lower than 0.1%, the reaction is terminated to obtain the phosphate-modified polyurethane acrylate; The modification process of the polybutadiene-modified polyurethane acrylate is as follows: 2.15 mol of toluene diisocyanate and 1 mol of polytetrahydrofuran diol are stirred and reacted at 500 r / min and 65 °C for 2 h, then 1 mol of polybutadiene is added and the reaction continues for 2 h. Finally, 2.2 mol of hydroxyethyl acrylate is added and the reaction proceeds for 4 h. When the NCO content in the system is lower than 0.1%, the reaction is terminated to obtain the polybutadiene-modified polyurethane acrylate; The reactive diluent is 30 parts by weight of isobornyl acrylate; The adhesion promoter is a titanate; The leveling agent is a polyether silicone copolymer, manufactured by BYK, with the product number BYK3760; The dispersant has a polymer chain segment with an amphiphilic molecular structure, which is an acrylic copolymer, manufactured by BYK, with the product number BYK-2013; The defoaming agent is a silicone-free defoaming agent, manufactured by Degussa, with the product number TEGO900; The pigment is 0.5 part by weight of phthalocyanine blue and 5 parts by weight of titanium dioxide; The filler includes 25 parts by weight of mica powder and 2 parts by weight of zinc phosphate; The photoinitiator includes 1.5 parts by weight of 2-hydroxy-2-methylpropiophenone and 1 part by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0081] This comparative example also provides a method for preparing the ultraviolet-curable flame-retardant composite resin material, including the following steps: Step 1: Place the phosphate-modified polyurethane acrylate, polybutadiene-modified polyurethane acrylate, reactive diluent, dispersant, and defoamer in a mixing tank and stir and mix them at 500 r / min for 3 min to obtain a mixed material; Step 2: Add the pigment and filler to the mixing tank, continue to stir and mix with the mixed material at 500 r / min for 3 min, and perform sanding after mixing evenly to obtain a fine material with a fineness < 15 μm; Step 3: Add the adhesion promoter, leveling agent, and photoinitiator to the mixing tank, continue to stir and mix with the fine material at 500 r / min for 3 min, and filter to obtain a liquid paint precursor; Step 4: After spraying the paint precursor into a film with a thickness of 120 μm, cure it at a speed of 5 m / min under an irradiation intensity of 500 mW / cm 2 , the spraying pressure is 1.5 bar, and the spraying distance is 15 cm to obtain the ultraviolet-curable flame-retardant composite resin material.
[0082] Comparative Example 3 This comparative example provides an ultraviolet-curable flame-retardant composite resin material, which is prepared by dissolving a modified acrylate in a reactive diluent, and then adding an adhesion promoter, leveling agent, dispersant, defoamer, pigment, filler, and photoinitiator and mixing them, and curing them by ultraviolet rays; the flame-retardant grade of the ultraviolet-curable flame-retardant composite resin material is V0, the adhesion grade is 0 level, and the pencil hardness is H; the insulation resistance of the ultraviolet-curable flame-retardant composite resin material > 1 GΩ, and the leakage current < 0.1 mA; After the ultraviolet-curable flame-retardant composite resin material is subjected to an impact resistance test, its electrical properties deteriorate. After the ultraviolet-curable flame-retardant composite resin material is subjected to bending resistance, electrolyte resistance, salt spray resistance test, temperature and humidity resistance, and thermal cycling resistance, the adhesion and pencil hardness remain unchanged, and there is no paint peeling, no crack, no bubbling, no peeling on the surface, and the insulation resistance and leakage current do not change. Moreover, the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the temperature and humidity resistance test is 13.2 MPa, and the bonding strength of the ultraviolet-curable flame-retardant composite resin material after the thermal cycling resistance test is 12.8 MPa.
[0083] In this comparative example, the modified acrylate includes phosphate-modified polyurethane acrylate and phenolic-modified acrylate, and the phenolic-modified acrylate is phenolic-modified epoxy acrylate.
[0084] In this comparative example, the components and their contents in the ultraviolet-curable flame-retardant composite resin material are as follows: Phosphate-modified polyurethane acrylate: 13 parts by weight; Phenolic-modified epoxy acrylate: 10 parts by weight; Reactive diluent: 30 parts by weight; Adhesion promoter: 5 parts by weight; Leveling agent: 0.5 parts by weight; Dispersant: 1 part by weight; Defoaming agent: 0.5 parts by weight; Pigment: 5.5 parts by weight; Filler: 27 parts by weight; Photoinitiator: 2.5 parts by weight; The preparation method of the phosphate-modified polyurethane acrylate is as follows: 2.15 mol of toluene diisocyanate and 1 mol of polytetrahydrofuran diol are stirred and reacted at 500 r / min and 65 °C for 2 h, then 1 mol of trimethylol phosphine oxide is added and the reaction continues for 2 h. Finally, 2.2 mol of hydroxyethyl acrylate is added and the reaction proceeds for 4 h. When the NCO content in the system is lower than 0.1%, the reaction ends to obtain the phosphate-modified polyurethane acrylate; The modification process of the phenolic-modified epoxy acrylate is as follows: At 40 °C, 1 mol of o-cresol novolac epoxy resin is added with 0.3% of benzyltriethylammonium chloride based on the total mass of the substances, 500 ppm of 4-methoxyphenol based on the total mass of the substances, and 100 ppm of phenothiazine based on the total mass of the substances. Then 1 mol of acrylic acid is added and continuous bubbling is carried out at 200 mL / min. The temperature is further raised to 80 °C and kept warm for 3 h. When the difference between the acid value in the system and the initial acid value is < 5 mg / KOH / g and the epoxy value is < 0.03, the reaction ends to obtain the phenolic-modified epoxy acrylate; The reactive diluent is 30 parts by weight of isobornyl acrylate; The adhesion promoter is titanate; The leveling agent is a polyether silicone copolymer, manufactured by BYK, with the product number BYK3760; The dispersant has a polymer chain segment with an amphiphilic molecular structure, which is an acrylic copolymer, manufactured by BYK, with the product number BYK-2013; The defoaming agent is a silicone-free defoaming agent, manufactured by Degussa, with the product number TEGO900; The pigment is 0.5 parts by weight of phthalocyanine blue and 5 parts by weight of titanium dioxide; The filler includes 25 parts by weight of mica powder and 2 parts by weight of zinc phosphate; The photoinitiator includes 1.5 parts by weight of 2-hydroxy-2-methylpropiophenone and 1 part by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0085] This comparative example also provides a method for preparing the ultraviolet-curable flame-retardant composite resin material, which includes the following steps: Step 1: Place the phosphate-modified polyurethane acrylate, phenolic-modified epoxy acrylate, reactive diluent, dispersant, and defoamer in a mixing tank and stir and mix them at 500 r / min for 3 min to obtain a mixed material; Step 2: Add the pigment and filler to the mixing tank, continue to stir and mix them with the mixed material at 500 r / min for 3 min, and perform sanding after mixing evenly to obtain a fine material with a fineness < 15 μm; Step 3: Add the adhesion promoter, leveling agent, and photoinitiator to the mixing tank, continue to stir and mix them with the fine material at 500 r / min for 3 min, and filter to obtain a liquid coating precursor; Step 4: After spraying the coating precursor into a film with a thickness of 120 μm, cure it at a speed of 5 m / min under an irradiation intensity of 500 mW / cm 2 , the spraying pressure is 3 bar, and the spraying distance is 20 cm to obtain the ultraviolet-curable flame-retardant composite resin material.
[0086] Table 1 shows the components and contents of the ultraviolet-curable flame-retardant composite resin materials in Examples 1-2 and Comparative Examples 1-3
[0087] Table 2 shows the performance tests of the ultraviolet-curable flame-retardant composite resin materials in Examples 1-2 and Comparative Examples 1-3
[0088] As can be seen from Table 2, the ultraviolet-curable flame-retardant composite resin material in the present invention has a high flame-retardant grade, strong adhesion, high hardness, good insulation, and no change in mechanical and electrical properties after tests such as impact, bending, temperature resistance, salt resistance, and electrolyte resistance, and has stable performance. However, in Comparative Example 1, after the phosphate-modified polyurethane acrylate was not added, the flame retardancy decreased significantly. In Comparative Example 2, after the phenolic-modified acrylate was not added, the hardness decreased, and bubbles were generated after testing, affecting the use effect. In Comparative Example 3, after the polyolefin-modified polyurethane acrylate was not added, the electrical properties were poor.
[0089] The test standard for the flame-retardant grade in the present invention is "UL94"; The test standard for the adhesion grade is the ISO grade, and the test method is: the cross-cut method. Use a cross-cut tool to make a cross-shaped grid with a side length of 1 mm on the paint surface, then stick and peel off with tape, and observe the peeling situation of the paint surface. Among them, the 0-grade standard is: there is no peeling at the grid edges after the test, and the incision edges are completely smooth; The test method for the pencil hardness is: rub the paint surface with pencil leads of different hardnesses (such as HB, H, or 2H), and observe whether there are scratches. The ultraviolet-curable flame-retardant composite resin material in the present invention has no scratches after being rubbed with HB, H, and / or 2H pencils; The test condition for the impact performance is that a 1 kg heavy object impacts the paint surface at a vertical distance of 50 cm; The test condition for the bending performance is to bend around a shaft rod with a curvature radius of 0.5 mm; The test condition for the electrolyte resistance is to soak in normal-temperature electrolyte for 30 days and in 85°C electrolyte for 4 h. The electrolyte is LB-315, with a pH of 4-6, and the main components are propylene carbonate, ethylene carbonate, ethyl methyl carbonate, and lithium hexafluorophosphate; The test condition for the salt spray resistance is to store under neutral salt spray conditions for 2000 h; The test condition for the temperature and humidity resistance is to store at 85°C and 85% RH for 2000 h; The test condition for the thermal cycling resistance is to perform thermal cycling from -40 to 85°C for 1000 h; The test standard for the bending performance is "GB / T1731-2020", the test standard for the salt spray resistance is "GB / T10125-2021", the test standard for the high temperature and humidity resistance is "GB / T2423.50-2012", and the test standard for the thermal cycling resistance is "GB / T2423.22-2012".
[0090] As can be seen from the above, the ultraviolet-curable flame-retardant composite resin material described in the present invention has a very wide range of uses, low cost, and extremely high market prospects.
[0091] The above is only a preferred embodiment of the present invention, and it is not a limitation of the present invention in any other form. Any modification or equivalent change made according to the technical essence of the present invention still belongs to the scope protected by the present invention.
Claims
1. A UV-curable flame-retardant composite resin material, characterized in that: The UV-curable flame-retardant composite resin material is prepared by dissolving a modified acrylate in a reactive diluent, adding an adhesion promoter, a leveling agent, a dispersant, a defoaming agent, a pigment, a filler and a photoinitiator, and then curing with UV light; the flame retardant grade of the UV-curable flame-retardant composite resin material is V0, the adhesion grade is 0, and the pencil hardness is H-2H; the insulation resistance of the UV-curable flame-retardant composite resin material is greater than 1GΩ, and the leakage current is less than 0.1mA; After the UV-curable flame-retardant composite resin material has been subjected to impact resistance, bending resistance, electrolyte resistance, salt spray resistance, temperature and humidity resistance, and hot and cold cycle resistance tests, the adhesion and pencil hardness remain unchanged, there is no paint exposure, cracks, bubbles, or shedding on the surface, and the insulation resistance and leakage current do not change. The bonding strength of the UV-curable flame-retardant composite resin material after the heat and humidity resistance test is 12-20MPa, and the bonding strength of the UV-curable flame-retardant composite resin material after the hot and cold cycle resistance test is 12-20MPa.
2. The UV-curable flame-retardant composite resin material according to claim 1, characterized in that: The modified acrylates include phosphate-modified polyurethane acrylates, phenol-modified acrylates and polyolefin-modified polyurethane acrylates.
3. The UV-curable flame-retardant composite resin material according to claim 2, characterized in that: The components and contents of the components in the UV-curable flame-retardant composite resin material are as follows: Phosphate modified polyurethane acrylate: 10-30 parts by weight; Phenolic modified acrylate: 10-30 parts by weight; Polyolefin modified polyurethane acrylate: 5-40 parts by weight; Active diluent: 20-60 parts by weight; Adhesion promoter: 1-8 parts by weight; Leveling agent: 0.1-0.5 parts by weight; Dispersant: 0.1-5 parts by weight; Defoaming agent: 0.1-5 parts by weight; Pigment: 1-20 parts by weight; Filler: 5-30 parts by weight; Photoinitiator: 1-8 parts by weight.
4. The UV-curable flame-retardant composite resin material according to claim 2, characterized in that: The preparation method of the phosphate-modified polyurethane acrylate is as follows: 2.0-2.15 mol of diisocyanate and 0.1-1 mol of polyol are stirred and reacted at 100-800 r / min and 40-85° C. for 0.5-4 h, and then 1-2 mol of phosphate compound is added and the reaction is continued for 0.5-4 h. Finally, 2.0-2.2 mol of end-capping agent is added and reacted for 2-6 h. When the NCO content of the system is lower than 0.1%, the reaction is terminated to obtain the phosphate-modified polyurethane acrylate.
5. The UV-curable flame-retardant composite resin material according to claim 4, characterized in that: The phosphate compound is one or more of trishydroxymethylphosphine oxide, tris(3-hydroxypropyl)phosphine oxide, tris(3-hydroxybutyl)phosphine oxide, di(3-hydroxypropyl)-n-propylphosphine oxide, di(3-hydroxypropyl)-n-butylphosphine oxide, di(3-hydroxypropyl)-sec-butylphosphine oxide, di(3-hydroxypropyl)phenylphosphine oxide, di(3-hydroxybutyl)ethylphosphine oxide and di(3-hydroxybutyl)-n-pentylphosphine oxide.
6. The UV-curable flame-retardant composite resin material according to claim 1, characterized in that: The photoinitiator includes one or more of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 4-chlorobenzophenone, methyl o-benzoylbenzoate, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, benzophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl) butanone, 2,2-dimethoxy-2-phenylacetophenone and 2-methyl-2-(4-morpholino)-1-[4-(methylthio)phenyl]-1-propanone.
7. A method for preparing the UV-curable flame-retardant composite resin material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, placing phosphate modified polyurethane acrylate, phenolic modified acrylate, polyolefin modified polyurethane acrylate, reactive diluent, dispersant and defoamer in a mixing tank, stirring and mixing to obtain a mixture; Step 2, adding pigment and filler into the mixing tank, continuing to stir and mix with the mixed material, and sand-grinding after mixing evenly to obtain fine material; Step 3, adding an adhesion promoter, a leveling agent and a photoinitiator into the mixing tank, continuing to stir and mix with the fine material, and filtering to obtain a liquid coating precursor; Step 4: spray the coating precursor into a film and then cure it to obtain the UV-curable flame-retardant composite resin material.
8. The preparation method according to claim 7, characterized in that: The fineness of the fine material in step 2 is less than 15 μm.
9. The preparation method according to claim 7, characterized in that: The curing speed in step 4 is 1-20 m / min, the curing method is ultraviolet curing, and the irradiation intensity of the ultraviolet light is 300-500 mW / cm 2 .
10. An electrical insulating outer layer, characterized in that The electrical insulation outer layer is prepared from the UV-curable flame-retardant composite resin material according to any one of claims 1 to 6.